MONITORING DAN EVALUASI CONTINUITY OF CARE PADA PENDERITA DIABETES MELLITUS TIPE 2 DI KLINIK WILAYAH SURABAYA TIMUR DAN SELATAN YANG MENGGUNAKAN BPJS KESEHATAN - Rona Rihadah; Lisa Aditama (CALYPTRA, 2018)
Abstract - Diabetes mellitus is a global health problem. Continuity of care has many benefits for the treatment of diabetic patient. BPJS Kesehatan implemented a tiered system in Indonesia. Health care transition is the one of risk mismatches treatment. This will affect the continuity of care the patient and also impact the quality of health services. Purpose: to determine the level perception and concerns about continuity of care patient diabetes mellitus type 2 in the east and south Surabaya clinics that use BPJS Kesehatan. The variables are the level of continuity if care on the type informational continuity, management continuity and relational continuity. And the problems in the continuity of care related transfer of information, coordination of care, ease of access to each level of care, and the relationship between patients and health professionals. The level of continuity of care can be measured by interview using a questionnaire CCAENA. Conclusion: 25 patients at the clinic in the research results is the level of continuity of care: 84% is very high (informational continuity: 72% is very high, management continuity: 84 % is very high, relational continuity: 92% is very high). Problems often occur there in continuity management is a long queue at hospital. While in clinic has no problems and lack participation of pharmacists in patient care.